Association Between ABO Blood Groups and Malaria Severity in a Regional Referral Hospital in Jayapura Papua, Indonesia - Andreas Pekey; Leonard Nainggolan; Cosphiadi Irawan; Kuntjoro Harimurti (Acta Medica Indonesiana)
Background: Malaria infection has caused a significant morbidity and mortality, notably in high-risk groups. Some evidence showed that ABO blood types might associate with malaria severity. This study aimed to determine the relationship between blood types and malaria severity in Papua, as Papua is a malaria-endemic area. Methods: A cross-sectional study was conducted in a regional referral hospital in Jayapura, Indonesia. Diagnosis of malaria was determined using World Health Organization criteria and classified into severe and uncomplicated malaria. Blood types were classified into O and non-O groups. Results: Out of 210 patients, 84 (40%) and 126 (60%) patients had non-O and O blood types, respectively. Severe malaria was more prevalent in non-O compared to O blood type (16.7% vs. 9.5%; the prevalence ratio (PR) was 2.4; 95% CI 1.06-6.42; p value 0.032). Amongst non-O groups, group B blood type demonstrated the highest incidence of severe malaria (p value 0.038; 95% CI: 1.06-6.42). Conclusion: There is an association between ABO blood group and the severity of malaria in Papua. Severe malaria was found more in non-O blood types, especially type B blood group.